COUNTY GOVERNMENT IN KENYA:Peoples’ awareness and perceptions of their governance systems and participation in their leadership and poverty-reduction projects. - Chitere, Preston Orieko (Advances in Social Sciences Research Journal, 2017)
County governments are relatively new in Kenya having been started in 2013. This study is a follow up on an earlier study of devolved governance in Kenya which we recently published. The objective of this study is to examine people’s awareness and perceptions of the county governance systems and participation in their leadership and poverty reduction projects. We purposively sampled 150 businesspersons and farmers and a few key informants from major towns of the three counties of Kakamega, Kisumu and Kajiado and interviewed them using interview schedules and interview guides. We also collected data from documentary sources. The counties and a majority of their residents were poor. Most of the respondents were aware of the leaders, responsibilities, advantages and problems of their county governments. Whereas the counties, especially Kakamega were implementing poverty reduction projects which were known by the respondents, about 95 per cent of them did not participate in them. Whereas Kakamega county system was positively- those of Kisumu and Kajiado were negatively perceived negatively by majority of the respondents as characterized by vices such as inefficiency, corruption and nepotism. There was urgent need for continuous education of the county leaders about good governance and residents about tolerance of other ethnic communities.